Assessment and comparison of clinical scar tenderness and imaging scar thickness for prediction of intraoperative scar integrity in pregnant patients with previous caesarean section - Pradhan, Shalini; Chakrabarti, Sekhar; Sehgal, Chandni; Shubham; Sakarkar, Neha; Kaur Sareen, Ravmeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Caesarean delivery rates have significantly risen over the past few decades, leading to an increase in the number of women with previous caesarean scars. In subsequent pregnancies, the integrity of uterine scar becomes an essential factor in decision making regarding the mode of delivery. Accurate assessment of scar integrity enables obstetricians to predict and mitigate the risks associated with vaginal birth after caesarean delivery. Several studies have independently demonstrated the reliability of scar tenderness and scar thickness in assessing uterine scar integrity; however, this study compares both these parameters for better prediction of the intraoperative scar integrity. Methods: 100 patients with history of previous LSCS were assessed for scar tenderness and third trimester’s sonographic LUS scar thickness and later on were taken up for caesarean section. Findings were correlated with intra-operative scar condition, whether the scar was intact or was compromised (scar dehiscence or rupture). Results: Scar thickness <2.5 mm demonstrated a sensitivity of 50%, specificity of 85%, positive predictive value of 60%, negative predictive value of 80%. Scar tenderness alone showed sensitivity of 66% and specificity of 71%, PPV of 60% and NPV of 82%. However, when both parameters were considered as combined criteria, the sensitivity improved to 74% and specificity increased to 96%, a higher PPV of 93% and an NPV of 86%. Conclusions: Combined assessment of clinical and sonographic parameters provides a more reliable method for identifying women at risk of uterine scar compromise during subsequent deliveries.